Adversity and redemption: Learning and teaching in the language learning histories of two EFL student-teachers - Baum, Miri Tashma (Studies in Second Language Learning and Teaching, 2015)
A better understanding of the multifaceted, dynamic and situated identity of the language learner stands at the center of much current SLA research. One of the main ways in which it is investigated is through the examination of autobiographical language learning histories. In an effort to better understand some of the processes which lead to a motivated, confident and successful language learner and user, this article analyzes the language learning histories of two EFL student-teachers, notable for their commitment to the learning and teaching of English. A close analysis of their narratives, focusing on thematic, stylistic and performative aspects, reveals what narrative psychologist McAdams (2006) has called “redemptive” patterns, that is, narrative structures in which hardship leads to inner growth and difficulties become “springboards” (Pals, 2006) to success. The two narrators also display a similar flexibility in their evolving self-positioning in response to the difficulties they narrate, and for both, attachment to the imagined community of Anglophone popular culture is an essential component in this process. Together, the learning experiences delineated in the accounts support the call for student-focused pedagogy, which puts emphasis on creating a positive emotional atmosphere, on the one hand, and providing rich intercultural knowledge, on the other.